Competition, Regulation and Privatisation: The Railroads and Telecommunications Network Industries in Germany - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2004)
In this paper we compare the privatisation and deregulation experience of German railroads with the telecommunications sector. In section 2 the period of nationalisation, legal entry barriers and self-regulation for the German railroad and the telecommunications sector is characterized. Section 3 is devoted to the privatisation and entry deregulation during the German telecommunications reform as well as the German railroad reform. In section 4 the need for a sector-symmetric regulatory approach is derived, with particular emphasis on the phasing-out potentials of sector specific regulation. It is shown that the problem of nondiscriminatory access has to be solved with respect of the railway infrastructure as a whole, whereas in telecommunications only the local loop may create a remaining regulatory problem.
Keywords: 330; Eisenbahnpolitik; Telekommunikationspolitik; Privatisierung; Deregulierung; Netzzugang; Vergleich; Deutschland